2014
DOI: 10.1177/000313481408001221
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Repair of Ileovesical Fistulas: Long-term Complications, Quality of Life, and Patient Satisfaction

Abstract: Ileovesical fistulas (IVFs) are an uncommon complication of Crohn's disease. The aim of this study is to compare long-term surgical outcomes, assess quality of life, and quantify patient satisfaction after IVF repair. A retrospective chart review followed by a prospective survey was carried out. Survey questions focused on patient satisfaction and quality of life after repair of IVF. Fifty-one patients were identified from an administrative database. Mean follow-up was 4.3 years with a response rate of 51 per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Factors that determine choice of treatment include severity of disease and symptoms, presence of complications such as abscess or bowel obstruction, and surgeon preference. 8 There are few studies from before the anti-TNF era evaluating surgical treatment for EVF. They showed that surgical treatment had good results with a low rate of complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors that determine choice of treatment include severity of disease and symptoms, presence of complications such as abscess or bowel obstruction, and surgeon preference. 8 There are few studies from before the anti-TNF era evaluating surgical treatment for EVF. They showed that surgical treatment had good results with a low rate of complications.…”
Section: Discussionmentioning
confidence: 99%
“…7 The most commonly cited etiology of ileovesical fistula (IVF) is CD, with an incidence of 2%. 8 Recurrent urinary tract symptoms, need for antibiotics, repeated hospital admissions, and poor quality of life prompt patients to request definitive therapy in both types of fistulas. With its relatively challenging anatomic location and the dense inflammatory process that often occludes the pelvis, some surgeons consider this disorder still as too technically challenging for laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 164 Meanwhile, it has been reported that most of the patients with ileovesical fistulas who underwent surgery showed improved quality of life during long-term follow-up. 165 Therefore, surgery is usually preferred for enterovesical fistulas; however, medical treatment can be considered in patients who already underwent multiple operations or are at high risk of short bowel syndrome.…”
Section: Treatment Of CD With Stricture or Fistulamentioning
confidence: 99%
“…Entero‐enteric fistulas are usually asymptomatic and require surgery only if they cause malabsorption or diarrhoea . For entero‐urogenital fistula, surgery is still superior to medical therapy, but again medial therapy may be attempted (see Sections and ).
…”
Section: Small Bowel Surgery In Crohn's Diseasementioning
confidence: 99%